Seeing red [compact disc, unabridged] - Brown, Sandra, 1948- (Hachette Audio, 2017)
Kerra Bailey is a TV journalist hot on the trail of a story guaranteed to skyrocket her career to new heights. Twenty-five years ago, Major Franklin Trapper became a national icon when he was photographed leading a handful of survivors to safety after the bombing of a Dallas hotel. For years, he gave frequent speeches and interviews but then suddenly dropped out of the public eye, shunning all media. Now Kerra is willing to use any means necessary to get an exclusive with the Major, even if she has to wrangle an introduction from his estranged son, former ATF agent John Trapper.